The Vanishing Act of Esme Lennox - O'Farrell, Maggie (1972-....). (London : Headline Publishing Group, 2020)
Edinburgh in the 1930s. The Lennox family is having trouble with its youngest daughter. Esme is outspoken, unconventionnal, and repeatedly embarrasses them in polite society. Something will have to be done. Years later, a young woman named Iris Lockhart receives a letter informing her that she has a great-aunt in a psychiatric unit who is about to be released. Iris has never heard of Esme Lennox and the one person who should know more, her grandmother Kitty, seems unable to answer Iris's questions. What could Esme have done to warrant a lifetime in an institution ? And how is it possible for a person to be so completely erased from a family's history ?
Keywords: Secretos de familia; Hospital -- Psiquiátrico; Edinburgh -- Anos 1930